USM FIRST UNIVERSITY IN THE NATION TO OFFER ARCHAEOTOURISM PACKAGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 23 March 2017 – The Centre for Global Archaeological Research (CGAR) at Universiti Sains Malaysia (USM) has launched the USM Archaeotourism Package in conjunction with its 30Year Celebration.